Levosimendan and Global Longitudinal Strain Assessment in Sepsis (GLASSES 1): a study protocol for an observational study - Iacopo Cappellini; Alessandra Melai; Lucia Zamidei; Maddalena Parise; Simone Cipani; Guglielmo Consales (BMJ Open)
Introduction Cardiogenic shock is a condition of low cardiac output that represents the end stage of a progressive deterioration of cardiac function. The main cause is ischaemic heart disease, but there are several non-ischaemic causes, including sepsis. The use of levosimendan in cardiogenic shock during sepsis is still under debate.Methods We are conducting an observational, single-centre, not-for-profit study enrolling patients aged 18–80 years old admitted to the intensive care unit with a diagnosis of septic shock. Patients will be monitored with the EV1000/VolumeView device (Edwards Lifesciences, Irvine, USA). Patients with cardiac index (CI) values <2.5 L/min/m2 and/or stroke volume index (SVI) <30 mL/beat/m2 are considered eligible for the study. Enrolled participants will undergo an echocardiographic examination using the Vivid S6 ultrasound machine (General Electric, Northville, Michigan) and a 3.6 MHz cardiology probe through which the apical projections of chambers 2, 3 and 4 will be acquired; this is necessary to calculate the global longitudinal strain (GLS) using EchoPAC* Clinical Workstation Software (General Electric). A dobutamine infusion will be started in these patients; 24 hours later CI and SVI will be recalculated using EV1000/VolumeView and then a levosimendan infusion will begin for 24 hours. Once the infusion cycle of the calcium-sensitising drug has been carried out, the infusion of dobutamine will be reduced until it stops, and the CI, SVI, GLS and arterial elastance (Ea):Ventricular Elastance (Ees) will be re-evaluated. The primary endpoint is recovery of GLS ≥15% and the secondary endpoint is a relative reduction in mortality of 15%.Ethics and dissemination The investigators declare that the study will be conducted in full compliance with international regulations (EU Directive 2016/679/EC) and national implementation (DM 15 July 1997; 211/2003; 200/2007) regarding the clinical trial and the principles of the Declaration of Helsinki. Study results will be disseminated through peer-reviewed journals and conferences. Ethical approval for this study has been given by Comitato Etico Regione Toscana - Area Vasta Centro, Florence, Italy (ethical committee number: 13875_oss) on 25 May 2019 (Chairperson Professor Marco Marchi).Trial registration number NCT04141410.